Optimal Placement of Advertisements on a Pixelated Web Banner. Issue 5 (2nd September 2016) - Gupta, Anshu; Aggarwal, Sugandha; Kaul, Arshia; Jha, P. C.
Abstract: The widespread usage of web applications has made it a popular medium of advertising, at the same time creating competition for advertising space. Web publishers seek to get maximum revenues utilising the advertisement space optimally. In this paper, a mathematical model is proposed to schedule the competing advertisements on multiple web banners with varying cost bids per pixel with a revenue maximization objective. A case study has been discussed to illustrate the application of the model and is solved using optimization software LINGO.